Influence of measurement processes on pressure-specific volume-temperature relationships of semi-crystalline polymer: Polypropylene. (September 2019) - Wang, Jian; Hopmann, Christian; Schmitz, Mauritius; Hohlweck, Tobias
Abstract: The pressure-specific volume-temperature (pvT) relationships of polymers are basic data for polymer engineering and polymer physics. The specific volume (vsp ) is not only defined by the current value of pressure (p) and temperature (T) but is also dependent on the process history of p and T. The influence of measurement processes on the pvT relationships of a semi-crystalline polymer, polypropylene (PP), has been studied using a piston-die pvT testing device. Based on the isobaric cooling/heating processes and the isothermal compression/decompression processes, the specific volume was examined as a function of cooling, heating, compression, decompression, cooling/heating rates and compression/decompression rates. The specific volume increases with increasing cooling rates in the crystallization and solid state, and decreases with increasing heating rates in the crystallization and molten state. The decompression process causes lower specific volume than the compression process. The specific volume decreases with increasing compression rates but decreases then increases with increasing decompression rates. Highlights: vsp measurements only show a moment in time of the processes. vsp in heating is different from that in cooling, at the same p and T. Cooling and heating rates have a large effect on the course of pvT. Compression leads to higher vsp than decompression, at the same p and T. pvT varies differently with different compression/decompression rates.